2017
DOI: 10.1002/smll.201701045
|View full text |Cite
|
Sign up to set email alerts
|

The Size Flexibility of Ferritin Nanocage Opens a New Way to Prepare Nanomaterials

Abstract: Ferritins are ubiquitous iron storage proteins where Fe(II) sequestration prevents not only its spontaneous oxidation to Fe(III) but also production of toxic free radicals. Recently, scientists have subverted these nature functions and used ferritin cage structures of nanometer dimensions for encapsulation of guest molecules such as anti-cancer drugs or bioactive nutrients based on pH induced ferritin disassembly and reassembly property. However, prior to this study, ferritin nanocage was required to disassemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 32 publications
(38 reference statements)
3
42
0
Order By: Relevance
“…If this is the case, one would expect that iron cores can be formed within 16-mer ∇C because of its shell-like structure, whereas NF-8 cannot due to its open structure. As expected, TEM analyses showed that iron cores with 500 iron/protein shells can be successfully generated with 16-mer ∇C as a biotemplate according to our reported method 33 ; however, such iron cores cannot be observed with NF-8 under the same experimental conditions (Supplementary Figure 10c, d); these findings approve the above conclusion that 16-mer ∇C has a shell-like structure. To clarify the disulfide connectivity for 16-mer ∇C , MS/MS analysis was performed according to a reported method 34 .…”
Section: Resultssupporting
confidence: 86%
“…If this is the case, one would expect that iron cores can be formed within 16-mer ∇C because of its shell-like structure, whereas NF-8 cannot due to its open structure. As expected, TEM analyses showed that iron cores with 500 iron/protein shells can be successfully generated with 16-mer ∇C as a biotemplate according to our reported method 33 ; however, such iron cores cannot be observed with NF-8 under the same experimental conditions (Supplementary Figure 10c, d); these findings approve the above conclusion that 16-mer ∇C has a shell-like structure. To clarify the disulfide connectivity for 16-mer ∇C , MS/MS analysis was performed according to a reported method 34 .…”
Section: Resultssupporting
confidence: 86%
“…Fluorescent imaging in vivo is of essential importance for practical applications, and thus we further investigated the bioimaging of 3Cys-ΔC-templated Au NCs by utilizing Caenorhabditis elegans as an animal model ( C. elegans is a kind of well-studied nematode with well-defined anatomy) [42, 43]. A series of worms at different cultivating times were fixed on glass slides and observed by laser confocal mircoscopy.…”
Section: Resultsmentioning
confidence: 99%
“…The inner surface of HsAFr is rich in acidic residues (Glu and Asp), resulting in a high negative charge density located at the inner cavity of HsAFr nanocage. Higher pH could lead to higher ionization of these free carboxyl groups and increasing electrostatic interaction of cationic drugs with the negatively charged inner cavity of the HsAFr nanocage [49,50]. As reported in literature, release of Gefitinib from apoferritin nanocage was examined at pH 7.5 over a period of 24 h. Rapid release of Gefitinib was observed during the first 6 h [51].…”
Section: Determination Of Ee and DLmentioning
confidence: 87%